Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1059840520901335
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Duration, Obesity, and School Failure Among Adolescents

Abstract: The aim of this study was to investigate the association between sleep duration, overweight/obesity, and school failure using data obtained from self-reported questionnaires completed by 13- to 15-year-olds in Sweden ( n = 1,363; 50.7% female). The height and weight of the participants were measured by school nurses. A multiple logistic regression analysis was used to analyze the association between sleep duration and overweight/obesity, school failure, and perceived economic situation. A short sleep duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Maladaptive eating (e.g., eating disorders) frequently persists in adulthood even in the face of significant deterioration in psychological and physiological wellness and overall quality of life [ 9 , 52 ]. It has a strong negative impact on family and social engagement and imposes substantial costs including health-care and social services costs [ 53 ] and non-health-care costs associated with obesity such as job or school absenteeism [ 54 ], thus increasing the risk of mental disorders and disordered eating development in the future [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maladaptive eating (e.g., eating disorders) frequently persists in adulthood even in the face of significant deterioration in psychological and physiological wellness and overall quality of life [ 9 , 52 ]. It has a strong negative impact on family and social engagement and imposes substantial costs including health-care and social services costs [ 53 ] and non-health-care costs associated with obesity such as job or school absenteeism [ 54 ], thus increasing the risk of mental disorders and disordered eating development in the future [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality is also a recurrent feature of student life and affects not only cognitive processes, but also recovery from stress and the elimination of fatigue, increasing the possibility of poor school performance [ 9 ]. Moreover, several studies have shown that sleeping problems including bad rest habits, correlate positively with both uncontrolled and emotional eating and substance use in differing populations [ 4 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting NPAG improves diverse aspects of health such as cognitive function, disease and longevity [ 1 , 2 , 17 ]. Health research pertaining to adolescents is heavily focused on school or university ages [ 25 , 26 , 27 , 28 ]. Minimal studies explore 16–18-year-olds, which is a key transitionary life stage important in reinforcing lifestyle trajectories, thereby deeming valuable the recognition of their physical activity levels and the behaviours influencing physical activity engagement.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study of 5560 children aged 10–11 years reported that a higher physical activity level was associated with longer (10 h) sleep duration [ 15 ]. Poor sleep was found to be a predictor of substance use among adolescents [ 16 ], and failed school courses were found to be more common in adolescents who slept less than seven hours during a night before school [ 17 ].…”
Section: Introductionmentioning
confidence: 99%